Trabecular bone score value in young men with ankylosing spondylitis - K. I. Kolpakov; E. A. Letyagina; V. O. Omelchenko; Yu. B. Ubshaeva; M. A. Korolev (Научно-практическая ревматология)
Aim – to investigate relationship of trabecular bone score (TBS) with activity and structural progression of ankylosing spondylitis (AS) in males younger than 50 years old without osteoporosis.Materials and methods. 26 male AS patients took part in the investigation. AS activity was evaluated by BASDAI and ASDAS-CRP indices, and highly sensitive C-reactive protein level. Structural AS progression was evaluated by sacroiliitis (SI). TBS was evaluated using the double-energy X-ray absoptiometry. Correlation between clinical measures and TBS was obtained using the Spearman r-criterion for quantitative variables and Kendall’s τ coefficientfor qualitative variables.Results. There was obtained no correlation between AS activity and TBS. Among clinical characteristics, SI stage was negatively correlated with TBS (τ=–0.313; p<0.05). Conclusion. TBS is associated with the severity of sacroiliitis in young AS male patients. Key words: ankylosing spondylitis, trabecular bone score, structural progression>˂ 0.05).Conclusion. TBS is associated with the severity of sacroiliitis in young AS male patients.